Study on the Pasture Establishment Technique VI. Effect of Different Spacings and Weedings on Establishment and Forage Production of Cenchrus ciliaris Linn., Lasiurus sindicus Henr. and Panicum antidotale Retz under arid condition - Chakravarty, A K; Verma, C M (Annals of Arid Zone, 2016)
The results of the experiments on spacing and weeding of the perennial grasses viz., Cenchrus ciliaris, Lasiurus sindicus and Panicum antidatale indicated increase in forage yield by 86, 120 and 284 per cent respectively from these grasses due to one weeding in the first year of their establishment. There was, however, no significant effect of spacings so far as the forage yield was concerned. The weedings indicated better growth in height, tillering and basal diameter of all the grasses whereas closer spacing (30 em) indicated better growth in L. sindicus and wider spacing (90 em) in P. antidatale.